Abnormal thyroid function is common in takotsubo syndrome and depends on two distinct mechanisms: results of a multicentre observational study. (12th November 2020) - Aweimer, A.; El‐Battrawy, I.; Akin, I.; Borggrefe, M.; Mügge, A.; Patsalis, P. C.; Urban, A.; Kummer, M.; Vasileva, S.; Stachon, A.; Hering, S.; Dietrich, J. W.
Abstract: Background: Several reports have described Takotsubo syndrome (TTS) secondary to thyrotoxicosis. A complex interaction of central and peripheral catecholamines with thyroid homeostasis has been suggested. In this study, we analysed sequential thyroid hormone profiles during the acute phase of TTS. Methods: Thyrotropin (TSH), free T4 (FT4) and free T3 (FT3) concentrations were analysed at predefined time points in 32 patients presenting with TTS or acute coronary syndrome (ACS, n = 16 in each group) in a 2‐year period in two German university hospitals. Data were compared to age‐ and sex‐matched controls (10 samples, each of 16 subjects), and an unsupervised machine learning (ML) algorithm identified patterns in the hormone signature. Subjects with thyroid disease and patients receiving amiodarone were excluded from follow‐up. Results: Among patients with TTS, FT4 concentrations were significantly higher when compared to controls or ACS. Four subjects (25%) suffered from subclinical or overt thyrotoxicosis. Two additional patients developed subclinical or overt thyrotoxicosis during stay in hospital. In four subjects (25%), FT4 concentrations were increased, despite nonsuppressed TSH concentration, representing an elevated set point of thyroid homeostasis. The thyroid hormone profile was normal in only six patients (38%) presenting with TTS. Conclusion: Abnormal thyroid function is frequent in patients with TTS. Primary hyperthyroidism and an elevated set point of thyroid homeostasis are common in TTS, suggesting a stress‐dependent endocrine response or type 2 thyroid allostasis. Thyroid function may be a worthwhile target in treating or preventing TTS. Abstract :